The Interaction Effect of Rivalry Restraint and Competitive Advantage on Profit: Why the Whole Is Less Than the Sum of the Parts - Makadok, Richard (Management Science, 2010)
Rivalry-restraint-based theoretical mechanisms predict that an industry's profits will increase when its firms engage in less price competition, or less direct competition, with each other. Competitive-advantage-based theoretical mechanisms predict that a firm's profits will increase when it creates superior economic value that direct and indirect competitors cannot fully compete away. But what is the interaction effect on profit of simultaneously restraining rivalry and increasing competitive advantage? Do they positively amplify/reinforce each other, or negatively dampen/undermine each other? This paper's theoretical model predicts a negative interaction effect, with potentially significant implications for theory, practice, and pedagogy.